Metabolic causes of nonimmune hydrops fetalis: A next-generation sequencing panel as a first-line investigation - Sudrié-Arnaud, Bénédicte; Marguet, Florent; Patrier, Sophie; Martinovic, Jelena; Louillet, Ferielle; Broux, Françoise; Charbonnier, Françoise; Dranguet, Hélène; Coutant, Sophie; Vezain, Myriam; Lanos, Raphaël; Tebani, Abdellah; et al. (Clinica chimica acta, 2018)
Hydrops fetalis is a life-threatening fetal condition, and 85% of all cases are classified as nonimmune hydrops fetalis (NIHF). Up to 15% of NIHF cases may be due to inborn errors of metabolism (IEM), but a large proportion of cases linked to metabolic disorders remains undiagnosed. This lack of diagnosis may be related to the limitations of conventional biological procedures, which involve sequential investigations and require multiple samples and steps. In addition, this approach is time consuming. We have developed a next-generation sequencing (NGS) panel to investigate metabolic causes of NIHF, ascites, and polyhydramnios associated to another fetal abnormality. The hydrops fetalis (HydFet) panel was designed to cover the coding regions and flanking intronic sequences of 41 genes. A retrospective study of amniotic fluid samples from 40 subjects was conducted. A prospective study was subsequently initiated, and six samples were analyzed using the NGS panel. Five IEM diagnoses were made using the HydFet panel (Niemann-Pick type C (NPC), Barth syndrome, HNF1Β deficiency, GM1 gangliosidosis, and Gaucher disease). This analysis also allowed the identification of 8p sequence triplication in an additional case. NGS combined with robust bioinformatics analyses is a useful tool for identifying the causative variants of NIHF. Subsequent functional characterization of the protein encoded by the altered gene and morphological studies may confirm the diagnosis. This paradigm shift allows a significant improvement of IEM diagnosis in NIHF. •An NGS-based panel with 41 genes is developed to investigate inborn errors of metabolism causes in non immune hydrops fetalis•An integrated NGS-based paradigm shift is proposed to significantly improve the diagnosis of non immune hydrops fetalis•Idiopathic non immune hydrops fetalis high rates are partially due to underestimated incidence of inborn errors of metabolism•This approach led to a significant improvement of inborn errors of metabolism diagnosis in non immune hydrops fetalis